The rural youth fertigation project at Dungun Terengganu / Nik Fakrulhazri Nik Hassan & Azemi Che Hamid - Nik Hassan, Nik Fakrulhazri; Che Hamid, Azemi (2016)
The Fertigation Dungun Rural Youth Project purposely to provide new knowledge regarding to fertigation system and business proposal to youth and helping them generate extra income. The implantation or methodology for this project was divided according to 4 phases. Phase 1 (6 months): To train graduate intern with fertigation knowledge by GM Peladang Sdn. Bhd. (from industry). Phase 2 (6 months): Intern Graduates will train youth who are identified to implement the program on site. Youth (participant) will be given the knowledge and skills of fertigation theoretically and practically. Phase 3: (6 months): Youth will be asked to switch crops. Graduate Intern will provide knowledge and skills in theoretical and practical. At last not least, Phase 4 (4 months): Youth will be asked to switch crops and the exchange of such plants can reduce the risk of a plant disease. The planting sites are conducted at Universiti Teknologi MARA (UiTM) Terengganu with supporting by Malaysian Academy of SME & Entrepreneurship Development (MASMED) and students from UiTM Terengganu My Agrosis Club. The youth involved are residents in the surrounding area Dungun. During this project the total of 6 rural youth has participated in addition Graduate Intern. At the same time, the issue of the difficulty to get good cooperation with the participants has affected the objectives of the project. The project was successful in order to channelling the cultivation methods and general knowledge about the fertigation system. Moreover, it is also boost up the motivation among the participants. Based on the implementation of these projects, the collection of information was carried out and found the cost of site and equipment preparation is a major cost. The total budget of the project is RM 139,272.90 and 63 percent of the cost is a come from the site preparation and planting activities. At the end of the project, a few activities was proposed to enhancing the agriculture activities at Taman MASMED such as introducing Pokok Kelapa Pandan (Cocos Nucifera - CN6) project, implementing Honey Kelulut (Trigona Stingless Bees Honey) and Mushroom farming project.